Facies and Architectural Element Analysis of Braided Fluvial Succession : The Paleogene Cawang Member, Ogan Komering Ulu Selatan Area , South Sumatra - Sapto Kis Daryono; Andi Kartika; Tridadi Saktiawan (Journal of Earth and Marine Technology (JEMT), 2025)
The Cawang Member of the Kikim Formation plays an important role in understanding the Paleogene sedimentary development of the Palembang Subbasin due to its presence as a pre-rift deposit that occurred before or simultaneously with the formation of the basin. Interpretations of the stratigraphic evolution of the Paleogene succession are based on detailed surface geological mapping, particularly through lithofacies identification and depositional environment analysis. These observations reveal that the lithological characteristics and facies distribution of the Cawang Member record dynamic sedimentary processes associated with early basin evolution. Facies analysis was conducted along measured stratigraphic sections encompassing conglomerate–sandstone 1 and sandstone 1-sandstone units exposed along the Bumi Agung and Batu Belang traverses in the South Ogan Komering Ulu area, South Sumatra. The conglomerate-sandstone 1 and sandstone 1-sandstone units attains a thickness of approximately 158.82 m, and about 177.50 m. A total of nine lithofacies were identified, including matrix-supported massive gravel (Gmm), matrix-supported, gravel (Gmg), massive gravel (Gm), massive sandstone (Sm), horizontally bedded sandstone (Sh), low-angle cross-bedded sandstone (SI), carbonaceous mud (C), massive fine sandstone-silt-mud (Fm), and massive siltstone and mudstone (Fsm). These lithofacies are grouped into four main facies associations: gravel bars (GB), sandy bedforms (SB), channels (CH), and overbank fine (FF). The assemblage of facies associations indicates deposition within a fluvial system dominated by braided river processes, with localized influence of sediment gravity flows